Bullying in the SUC's Classroom: A Hidden Epidemic? - Clores, Novy R. (Future Science / FSH-PH Publications, 2023)
Several literatures have already pointed to the effects of bullying to the learners’ journey in educational institution. Acts of bullying have even evolved from the actual or physical acts to virtual acts brought by the ever increasing ICT saturation around the world. The study explored the prevalence of bullying in SUCs by looking into the profile, the personal interpretation of bullying, the prevalence of bullying in the classroom, the effects of bullying, and the awareness on policies of bullying among tertiary students. Using cross-sectional survey method with a questionnaire as the main instrument, 95 respondents were tapped. For the findings, majority of the respondents were females aged 18 – 24 years old, Varied definitions of bullying were presented indicating that these acts are done in multiple and in combination of ways by the perpetrators. The most dominant effects of bullying were low self-esteem, depression, shyness, perceived negative school climate and wanting to be left alone. These effects somehow diminished the motivation or desire of the learner to further seeking knowledge in school. Furthermore, learners expressed their frustration and interest in reaching their dreams and aspirations. One of the academic heads of the institution expressed during the interview that while there are existing policies in the institution against bullying, reporting cases of bullying is often problematic. This implies that responsible office could not immediately act on it unless victims come forward. Some said that bullying is part of the growing process and taking it seriously is a sign of immaturity thus it should not be considered as big deal. With respect of the EQ of the victims and non – victims there were significant differences in Self awareness, self motivation and empathy and no significant differences on managing emotions and social skills implying the victims are effective in keeping it among themselves. In conclusion, bullying is prevalent in SUCs and it is the method of reporting of cases that causes a seemingly lack of action on the part of the authorities. It is therefore recommended that inclusion of reporting mechanism and vigorous campaign against bullying must be included in the school academic manual. Furthermore, everyone in the institution should work hand in hand to halt this hidden epidemic.